Vaccination generates functional progenitor tumor-specific CD8 T cells and long-term tumor control - Mary Philip; Mary K Washington; Joseph T Roland; Carlos R Detrés Román; Megan M Erwin; Michael W Rudloff; Frank Revetta; Kristen A Murray; Natalie R Favret; Jessica J Roetman (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint blockade (ICB) therapies are an important treatment for patients with advanced cancers; however, only a subset of patients with certain types of cancer achieve durable remission. Cancer vaccines are an attractive strategy to boost patient immune responses, but less is known about whether and how immunization can induce long-term tumor immune reprogramming and arrest cancer progression. We developed a clinically relevant genetic cancer mouse model in which hepatocytes sporadically undergo oncogenic transformation. We compared how tumor-specific CD8 T cells (TST) differentiated in mice with early sporadic lesions as compared with late lesions and tested how immunotherapeutic strategies, including vaccination and ICB, impact TST function and liver cancer progression.Methods Mice with a germline floxed allele of the SV40 large T antigen (TAG) undergo spontaneous recombination and activation of the TAG oncogene, leading to rare early cancerous TAG-expressing lesions that inevitably progress to established liver cancer. We assessed the immunophenotype (CD44, PD1, TCF1, and TOX expression) and function (TNFα and IFNγ cytokine production) of tumor/TAG-specific CD8 T cells in mice with early and late liver lesions by flow cytometry. We vaccinated mice, either alone or in combination with ICB, to test whether these immunotherapeutic interventions could stop liver cancer progression and improve survival.Results In mice with early lesions, a subset of TST were PD1+ TCF1+ TOX− and could produce IFNγ while TST present in mice with late liver cancers were PD1+ TCF1lo/− TOX+ and unable to make effector cytokines. Strikingly, vaccination with attenuated TAG epitope-expressing Listeria monocytogenes (LMTAG) blocked liver cancer development and led to a population of TST that were PD1-heterogeneous, TCF1+ TOX− and polyfunctional cytokine producers. Vaccine-elicited TCF1+TST could self-renew and differentiate, establishing them as progenitor TST. In contrast, ICB administration did not slow cancer progression or improve LMTAG vaccine efficacy.Conclusion Vaccination, but not ICB, generated a population of functional progenitor TST and halted cancer progression in a clinically relevant model of sporadic liver cancer. In patients with early cancers or at high risk of cancer recurrence, immunization may be the most effective strategy.